2002
DOI: 10.1111/0162-895x.00273
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Civic Orientation Among American Youth: Trust, Religiious Valuation, and Attributions of Responsibility

Abstract: This study identified affective and cognitive factors predicting American 6th, 8th, and 10th graders' civic orientation, defined here as feelings of effective community service, conceptualizations of citizenship, and participation in student government. Independent variables included measures of interpersonal trust, valuation of religion, and individualistic versus collective action attributions of responsibility for solving social problems. Interpersonal trust predicted four out of the five outcome variables.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…More recently, it has been found that involvement in formal groups (e.g., religious groups, sports groups, etc.) in which the individual is able to take on active and specific roles is related to prosocial-oriented civic participation (Albanesi, Cicognani & Zani, 2007), young people who belong to a club or team are much more likely to be involved in community service two years later (Hart, Atkins & Ford, 1998), people who have high levels of religious attendance and religious activity are more likely to be civically and politically active (Crystal & DeBell, 2002;Verba, et al, 1995;Youniss, McClellan, Su & Yates, 1999;Zaff, et al, 2008;Zukin, et al, 2006), and young people who participate in community-based organizations and in extra-curricular activities are more likely to participate both civically and politically in later life (Glanville, 1999;Otto, 1975;Verba, et al, 1995;Youniss, McClellan & Yates, 1997;Zaff, et al, 2008;Zaff, Moore, Papillo & Williams, 2003).…”
Section: Social Factorsmentioning
confidence: 99%
“…More recently, it has been found that involvement in formal groups (e.g., religious groups, sports groups, etc.) in which the individual is able to take on active and specific roles is related to prosocial-oriented civic participation (Albanesi, Cicognani & Zani, 2007), young people who belong to a club or team are much more likely to be involved in community service two years later (Hart, Atkins & Ford, 1998), people who have high levels of religious attendance and religious activity are more likely to be civically and politically active (Crystal & DeBell, 2002;Verba, et al, 1995;Youniss, McClellan, Su & Yates, 1999;Zaff, et al, 2008;Zukin, et al, 2006), and young people who participate in community-based organizations and in extra-curricular activities are more likely to participate both civically and politically in later life (Glanville, 1999;Otto, 1975;Verba, et al, 1995;Youniss, McClellan & Yates, 1997;Zaff, et al, 2008;Zaff, Moore, Papillo & Williams, 2003).…”
Section: Social Factorsmentioning
confidence: 99%
“…Beyond that, trust is related to people's civic orientations (Brehm & Rahn, 1997;Crystal & DeBell, 2002); therefore, a truly civic organization such as the military should be especially attentive to issues of trust.…”
Section: Martial Virtue and Trustmentioning
confidence: 99%
“…Thus, three distinct categories of analysis, or dimensions, concerning citizenship emerge from the literature: civic knowledge, civic attitudes, and civic behavior. Crystal and DeBell (2002) invoked Putnam, citing the decline of civic engagement, especially among youth (Putnam, 1995a(Putnam, , 1995b as one of the reasons for needing a "successful model of civic/political participation . .…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research questions in this study employed Crystal and DeBell's (2002) concept of civic orientation, which was divided into two dimensions: attitudes and behaviors. Civic attitudes refers to one's disposition toward government and society.…”
Section: Survey Instrumentmentioning
confidence: 99%